2021
DOI: 10.1088/1742-6596/1899/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

Regional Overview of Food Security from Two Dimensions: Availability and Access to Food, East Java Province

Abstract: Food security has always been a topic of keen interest to policy-makers, practitioners, and academics worldwide. In the operational sense, food security concerns the availability, accessibility, and stability of its procurement. The leading indicators of food security at the household level access (physical and economic) to food, food availability and risks associated with food access and availability. A study was conducted by utilizing data from several government institutions to examine the level of regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Currently, it is reported that only 4 Grand Parent stocks are managed in Malaysia (Ferlito, 2020), and very limited information can be found on Great GrandParent or pureline maintenance in the country. The maintenance of pure lines and pedigree selection, such as in figure 2, should also be considered part of good food security practices (Lisanty et al, 2021). Apart from the common commercialised chicken such as Legohorn, Rhode Island Reds, Cobbs Chicken and White Recessive Rocks (Wang et al, 2021), a good example is the development of the Haebara Breed of Chicken, which was developed to support the supply of halal non-Genetically Modified Organism (GMO) poultry breeds without antibiotics nor vaccination, currently in its prototype and implemented in Myanmar (Exclusive Interview With Mr Zuraimi Jumaat, 2022).…”
Section: Breeding and Geneticsmentioning
confidence: 99%
“…Currently, it is reported that only 4 Grand Parent stocks are managed in Malaysia (Ferlito, 2020), and very limited information can be found on Great GrandParent or pureline maintenance in the country. The maintenance of pure lines and pedigree selection, such as in figure 2, should also be considered part of good food security practices (Lisanty et al, 2021). Apart from the common commercialised chicken such as Legohorn, Rhode Island Reds, Cobbs Chicken and White Recessive Rocks (Wang et al, 2021), a good example is the development of the Haebara Breed of Chicken, which was developed to support the supply of halal non-Genetically Modified Organism (GMO) poultry breeds without antibiotics nor vaccination, currently in its prototype and implemented in Myanmar (Exclusive Interview With Mr Zuraimi Jumaat, 2022).…”
Section: Breeding and Geneticsmentioning
confidence: 99%
“…sektor penunjang perekonomian bangsa, pertanian berperan penting dalam penyedia pangan dan lapangan kerja (Lisanty et al, 2021). Menurut Annet (2014), bahan mentah untuk kebutuhan industri juga turut dipegang peranannya oleh sektor pertanian, selain untuk komoditi ekspor.…”
Section: Selakuunclassified
“…The economic turmoil that occurred due to the Covid-19 pandemic that hit countries in the world, became a historical moment, especially for people in Indonesia (Lisanty, 2021). The impact of the Covid-19 pandemic on the economy of the Indonesian people was enormous, which among other things resulted in a decline of around 60% in household consumption or people's purchasing power, prolonged uncertainty, resulting weak investment, business stoppages, and economic slowdown which caused commodity prices to fall and Indonesia exports to several countries also stopped too (Lisanty, Andajani, et al, 2021;Susilawati et al, 2020).…”
Section: Introductionmentioning
confidence: 99%